Taxonomy and distribution of Sternotrigon Skopin in China (Coleoptera, Tenebrionidae) - Ba, Yi-Bin; Ren, Guo-Dong (Zootaxa, 2013)
Sternotrigon Skopin is reviewed. One new species, Sternotrigon albipulis sp. nov., is described and Sternotrigon zichyi Csiki, 1901 is newly recorded in China. A key to the species of Sternotrigon is included. Species of Sternotrigon are divided into two distributional types: an Inner Asian and Mongolian tableland type; the distribution pattern is briefly described. The type and other materials examined are deposited in the Museum of Hebei University (MHBU), Baoding, China.